THE CORRELATION BETWEEN LEARNING INTEREST AND LEARNING OUTCOME OF ENGINEERING DRAWING COURSE OF CLASS X STUDENTS OF BUILDING DRAWING ENGINEERING DEPARTMENT AT SMK N 1 SUMATERA BARAT - 1781-1796 , Dana Yulianto (CIVED, 2016)
This research was aimed to reveal the correlation between learning interest and learning outcome of Engineering Drawing Course of Class X Students of Building Drawing Engineering Department at SMK N 1 Sumatera Barat. The type of the research was a correlational research and the population was all 31 students of Class X of Building Drawing Engineering Department academic year 2015/2016.  The sample was taken by using total sampling technique.  Primary data was obtained from the questionnaires about learning interest which were distributed to the students, and secondary data was the learning outcome of students on Drawing Engineering course. The techniques of data analysis used were: (1) Descriptive analysis, (2) Analysis requirement test, and (3) The hypothesis test. From the analysis result, it can be concluded that there is a significant and strong enough correlation between learning interest and learning outcome of Engineering Drawing course of Class X Students of Building Drawing Engineering Department at SMK N 1 Sumatera Barat with 95% level of confidence. Keywords: Learning interest, Learning outcome